Self-nanoemulsifying drug delivery system (SNEDDS) of Amomum compactum essential oil: Design, formulation, and characterization - Tri Ujilestari, Ronny Martien, Bambang Ariyadi, Nanung Danar Dono, Zuprizal (Journal of Applied Pharmaceutical Science, 2018)
The main purpose of this study was to formulate and to characterize a self-nanoemulsifying drug delivery systems of cardamom (Amomum compactum) essential oil. The optimum formula was analyzed using a D-Optimal mixture designed by varying concentrations of oil component (Amomum compactum essential oil and virgin coconut oil), Tween 80, and polyethylene glycol 400 (PEG 400) (v/v) using a Design Expert® Ver. 7.1.5. Emulsification time and transmittance were selected as responses for optimization. The optimum formula was characterized by droplet size, zeta potential, viscosity, thermodynamic stability, and morphology using Transmission Electron Microscopy. SNEDDS of Amomum compactum essential oil was successfully formulated to SNEDDS using 10% of Amomum compactum essential oil, 10% of virgin coconut oil, 65.71% of Tween 80, and 14.29% of PEG 400. The characterization result showed the percent transmittance 99.37 ± 0.06, emulsification time 46.38 ± 0.61 s, the average droplet size 13.97 ± 0.31 nm with PI 0.06 ± 0.05, zeta potential −28.8 to −45.9 mV, viscosity 187.5 ± 0 mPa•s, passed the thermodynamic stress tests, and indicated spherical shape. The study revealed that the formulation has increased solubility and stability of Amomum compactum essential oil.
Keywords: Amomum compactum, essential oil, self-nano emulsifying drug delivery system, D-optimal mixture design.